Bulky primary tibia mantle cell lymphoma achieved complete remission with CHOP and DHAP plus rituximab: A case report - Chen, Si (Oncol Lett, 2018)
Mantle cell lymphoma (MCL) is a subtype of B-cell non-Hodgkin lymphoma. Heterogeneous and extensive lymphadenopathy is the most common clinical manifestation. Although skeletal involvement is not uncommon in other types of non-Hodgkin lymphoma, primary bone MCL is rare. The present study reported a case of primary tibia MCL in a 50-year-old male presenting with left tibia pain and a rapidly growing lump. Computed tomography and magnetic resonance imaging scans revealed a progressive lesion in the cortical bone and surrounding soft tissue mass. A positron emission computed tomography scan demonstrated increased glucose metabolism in the middle tibia without involvement of regional lymph nodes. An aspiration biopsy was performed, and pathological examination revealed small-medium sized cells strongly positive for cluster of differentiation (CD)5, CD20 and cyclin D1. Fluorescent in situ hybridization analysis confirmed the presence of immunoglobulin heavy chain/cyclin D1 gene fusion formed by t(11;14) translocation. As a result, primary bone MCL was diagnosed and rituximab-containing chemotherapy was administered. Following complete remission, autologous hemopoietic stem cell transplantation and rituximab maintenance therapy were performed. During the 2-year follow-up period, the patient remained in a good condition without signs of relapse.